Plant Communities and Their Environment - Oliveira, Manuel T.; Candan, Feyza; Fernandes-Silva, Anabela (IntechOpen, 2020)
This book presents different perspectives on how to understand the complex interaction between plants and the environment. Plant communities adapt to biotic and abiotic stresses with different mechanisms and understanding these phenomena provides the means to better manage our environment and to cultivate crops that better serve our needs.